Strategi Pembangunan Koperasi Pertanian Alpukat Berbasis Syariah Pendekatan ANP-BOCR - Fatikhah Fatikhah; Ahmad Mulyadi Kosim; Abrista Devi (Al Maal: Journal of Islamic Economics and Banking, 2020)
Interest in the study is to determine the benefits, opportunity, cost, risk and strategic alternatives in decision-making in the development of agricultural cooperatives.This study uses research methods analytic network process (ANP) with the benefits of network opportunity cost risk (BOCR). Data collection is done through in-depth interviews (indepth interview) and questionnaires by respondents. The results of this study indicate that on a priority basis the decision of the respondents would provide benefits to agriculture avocado compared with the costs and risks of the construction decision for agricultural cooperatives avocado. Based on the strategic priorities in the development of agricultural cooperatives are SDM and knowledge of cooperatives.